Optimal Capacitor Placement Using ICA and comparison with PSO Method; Case Study in KERMAN - Mahdi Mozaffari Legha (Journal of Global Pharma Technology, 2017)
Increasing application of capacitor banks on distribution networks is the direct impact of development of technology and the energy disasters that the world is encountering. Line loss reduction is one of the major benefits of capacitor, amongst many others, when incorporated in the power distribution system. The quantum of the line loss reduction should be exactly known to assess the effectiveness of the distributed generation. In this paper, a new method is proposed to find the optimal and simultaneous place and capacity of these resources to reduce losses, improve voltage profile too the total loss of a practical distribution system is calculated with and without capacitor placement and an index, quantifying the total line loss reduction is proposed. This results in saving substantial amount of energy. To reduce our objective function, we find optimized type of conductor by taking use of Imperialism Competitive Algorithm (ICA) method and comparison with PSO method. To demonstrate the validity of the proposed algorithm, computer simulations are carried out on actual power network of Kerman Province, Iran and the simulation results are presented and discussed.Keyword: Distribution systems, Loss reduction index, Capacitor placement, Imperialist Competitive Algorithm